FUNGSI MANAJEMEN KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU DI MADRASAH ALIYAH HIDAYATUL MUBTADIIN - Warmidianti; Asrori, Achmad; Imamah, Yuli Habibatul (UNISAN JURNAL, 2023)
The purpose of this study was to find out and describe about: 1) The management function of the Madrasah head in improving the performance of MA Hidayatul Mubtadiin teachers. 2) Supporting factors and inhibiting factors for the performance of MA Hidayatul Mubtadiin teachers. This type of research is a qualitative research and is descriptive in nature, namely research that describes the management function of the Madrasah head in improving the performance of MA Hidayatul Mubtadiin teachers. Sources of data in this study are: (1) Primary data, consisting of Madrasah heads, deputy Madrasah heads, staff/employees, teachers; (2) Secondary data, obtained from library research and documentation. Data collection methods in this study are observation, interviews, and documentation. The method of data analysis is done by processing data (selecting, classifying, summarizing results, and making data reduction). The results of the study show that the head of the Madrasah has carried out the stages of the management function well from the planning stage to the control (Controlling), however, sometimes there are obstacles in the implementation, this is due to the lack of professional teachers, minimal infrastructure, and teachers who do not understand the RPP. and reluctance to make lesson plans, lack of teacher awareness of discipline in teaching. Teacher's ability to evaluate learning is not yet comprehensive, because it still leads to cognitive and psychomotor aspects that are not given enough attention. Good management of Madrasah heads can improve teacher performance, both in planning, implementing and evaluation . This can be seen from the increase in teacher discipline in teaching, the learning tools owned by teachers are getting better and more complete. Factors supporting the performance of MA Hidayatul Mubtadiin teachers include: sincerity to work, respect for teachers and factors inhibiting teacher performance include: minimal facilities and infrastructure.